Comparative hemodynamic responses to upright and recumbent cycling in patients with exercise intolerance - Albulushi, Arif; Al Harthi, Faisal; Aly, Gamal; Al-Wahshi, Yahya; El-Deeb, Mohammed H. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionUnderstanding the influence of body position on cardiovascular responses during exercise is crucial for precise diagnostic and therapeutic strategies, particularly in patients with exercise intolerance.AimThis study aims to compare the hemodynamic responses to exercise in upright and recumbent cycling positions in patients with exercise intolerance.MethodsA cross-over study design was employed, enrolling 21 patients for right heart catheterization during exercise in both upright and recumbent positions. Hemodynamic variables were measured at rest and across various exercise intensities.ResultsSignificant differences were observed in right atrial pressure (RAP), mean pulmonary artery pressure (mPAP), and pulmonary artery wedge pressure (PAWP) between upright and recumbent positions. Upright exercise revealed lower values of RAP, mPAP, and PAWP, indicating distinct hemodynamic profiles.ConclusionBody position significantly affects cardiovascular dynamics during exercise, providing valuable insights for diagnosing and managing exercise intolerance.